Digitalization in entrepreneurship education and its effect on entrepreneurial capacity building - Ákos Tóth-Pajor; Zsolt Bedő; Vivien Csapi (Cogent Business & Management, 2023)
Entrepreneurship education, the process of knowledge, skill, competency, and attitude development, aims to maximize the effectiveness of the entrepreneurial capacity building. The pandemic boosted the digital transformation of higher education and brought the online incubation platform NETMIB to life. This paper introduces this unique platform solution and utilizes online opportunities for skill and attitude assessment. An online survey-based research method was applied, and an online Entrepreneurial Orientation (EO) Index was developed as a valid scale for measuring entrepreneurial attitudes in online incubation programs. Based on the findings, student idea owners in the online incubation process have a significantly higher propensity to engage in business activities and a stronger desire for independence and achievement. The findings of this paper can contribute to the targeting and development of educational interventions in the incubation programs, and the online EO Index can be a useful tool among the performance measures of various incubation programs. Summary: Entrepreneurship education, the process of knowledge, skill, competency, and attitude development, aims to maximize the effectiveness of the entrepreneurial capacity building. The pandemic boosted the digital transformation of higher education and brought the online incubation platform NETMIB (Network of multidisciplinary ideation and business model generation) to life. This paper introduces this unique platform solution of online incubation and utilizes online opportunities for skill and attitude assessment. Since education aims to influence entrepreneurial capacity, measured by attitudes, the paper develops a self-assessment tool for online entrepreneurship education. Hypothesizes that there are significant differences in the attitudes of the members according to their role in the online incubation process. An online survey-based research method was used, and an entrepreneurial attitude construct was created concerning the member's desire for innovation, personal control, achievement, and self-esteem. Based on the findings, student idea owners in the online incubation process have a significantly higher propensity to engage in business activities and a stronger desire for independence and achievement. The findings of this paper contribute to the targeting and development of educational interventions in incubation programs, and the online Entrepreneurial Orientation Index can be a useful tool among the performance measures of various incubation programs.
Keywords: I23; L26; 650; digitalization; entrepreneurial attitudes; entrepreneurial capacity building; entrepreneurship education; online education